2023
DOI: 10.1093/ee/nvad005
|View full text |Cite
|
Sign up to set email alerts
|

Osmia taurus (Hymenoptera: Megachilidae): A Non-native Bee Species With Invasiveness Potential in North America

Abstract: Bees are important pollinators and are essential for the reproduction of many plants in natural and agricultural ecosystems. However, bees can have adverse ecological effects when introduced to areas outside of their native geographic ranges. Dozens of non-native bee species are currently found in North America and have raised concerns about their potential role in the decline of native bee populations. Osmia taurus Smith (Hymenoptera: Megachilidae) is a mason bee native to eastern Asia that was first reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…At present, there has been little monitoring of native megachilid communities to determine their population trajectories in the added presence of closely‐related non‐native competitors. Our results suggest the spillover of non‐native fungi to multiple native mason bee species from co‐introduced non‐native mason bee species may offer insight regarding observed regional declines in six native Osmia species (Gutierrez et al, 2023; LeCroy et al, 2020). With increasing use of “bee hotels” by the public (Fortel et al, 2016; González‐Zamora et al, 2021), without periodic cleaning, these nesting cavities could cause hotspots of Ascosphaera buildup and high rates of infection, serving as points of Ascosphaera spillover to native mason bees.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…At present, there has been little monitoring of native megachilid communities to determine their population trajectories in the added presence of closely‐related non‐native competitors. Our results suggest the spillover of non‐native fungi to multiple native mason bee species from co‐introduced non‐native mason bee species may offer insight regarding observed regional declines in six native Osmia species (Gutierrez et al, 2023; LeCroy et al, 2020). With increasing use of “bee hotels” by the public (Fortel et al, 2016; González‐Zamora et al, 2021), without periodic cleaning, these nesting cavities could cause hotspots of Ascosphaera buildup and high rates of infection, serving as points of Ascosphaera spillover to native mason bees.…”
Section: Discussionmentioning
confidence: 76%
“…At present, there has been little monitoring of native megachilid communities to determine their population trajectories in the added presence of closely-related non-native competitors. Our results suggest the spillover of non-native fungi to multiple native mason bee species from co-introduced non-native mason bee species may offer insight regarding observed regional declines in six native Osmia species (Gutierrez et al, 2023;LeCroy et al, 2020).…”
Section: Discussionmentioning
confidence: 82%
“…To evaluate potential range expansion dynamics for O. cornuta , we examined the historical pattern of North American establishment of the closely related non-natives O. cornifrons and O. taurus . Prior studies have shown that O. cornifrons and O. taurus widely expanded throughout the eastern US following introduction and establishment (Gutierrez et al 2023, LeCroy et al 2020, MacIvor et al 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Both species have broadly increased their range in the last 20 years. Their shared range now extends from the Carolinas to southern Ontario and west into several midwestern states (Gutierrez et al 2023, MacIvor et al 2022). Osmia taurus observations reach as far south as Georgia and Florida, and O. cornifrons records extend west to Colorado, Utah, and Oregon (Gutierrez et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…It is unknown when O. taurus was introduced to North America but is thought to have occurred in 1973 with the intentional introduction of Osmia cornifrons (Radoszkowski, 1887) for pollination (Batra 1979, Gibbs et al 2017), suggesting species can be present for decades before suddenly becoming widely distributed. Alternatively, given the rapid spread of this species since its detection in 2002, others argue it is likely a more recent introduction than previously thought (Gutierrez et al 2023). These observed patterns are not restricted to non-native bees.…”
Section: Discussionmentioning
confidence: 99%